Phylogenetic analysis of Xanthomonas translucens & genome-enabled diagnostic tools for pathogens of cereals and non-cereals - Langlois, Paul, author; Leach, Jan, advisor; Jahn, Courtney, committee member; Steingraeber, David, committee member (Colorado State University. Libraries, 2016)
Prevalence of Xanthomonas translucens, which causes bacterial leaf streak (BLS) in cereal crops and bacterial wilt in forage and turfgrass species, has increased in many regions in recent years. Because the pathogen is seedborne in economically important cereals, it is a concern for international and interstate germplasm exchange, and thus, reliable and robust protocols for its detection in seed are needed. However, historical confusion in the taxonomy within the species has complicated the development of accurate and reliable diagnostic tools for X. translucens. The goal of this study was to clarify the genetic relationships of X. translucens pathovars, and to use that information to develop useful and robust diagnostic tools. We sequenced genomes of 15 X. translucens isolates representing six different pathovars. Based on Multilocus Sequence Typing (MLST), wheat isolates designated as X. translucens pv. undulosa are in the same phylogenetic clade as barley isolates identified as X. translucens pv. translucens. The wheat and barley pathovars, undulosa and translucens, are genetically distinct from the cerealis pathovar isolated from either cereals or non-cereals, as well as pathovars isolated from other non-cereals, including arrhenatheri, graminis, and poae. Using unique genomic regions, Loop Mediated Isothermal Amplification (LAMP) primer sets were designed that selectively amplified X. translucens (species-specific), or that selectively amplified strains belonging to cerealis and poae pathovars. In addition, LAMP PCR assays were developed that distinguished X. translucens strains associated with cereal leaf streak (CLS), such as undulosa, translucens, hordei, and secalis, from the other cereal or non-cereal pathovars.
Keywords: barley; LAMP; wheat; diagnostics; bacteria; phylogenetics